LIMITATIONS OF SIZE AND LEVELS TESTS OF WRITTEN RECEPTIVE VOCABULARY KNOWLEDGE. Issue 1 (29th March 2021) - Stoeckel, Tim; McLean, Stuart; Nation, Paul
Abstract: Two commonly used test types to assess vocabulary knowledge for the purpose of reading are size and levels tests. This article first reviews several frequently stated purposes of such tests (e.g., materials selection, tracking vocabulary growth) and provides a reasoned argument for the precision needed to serve such purposes. Then three sources of inaccuracy in existing tests are examined: the overestimation of lexical knowledge from guessing or use of test strategies under meaning-recognition item formats; the overestimation of vocabulary knowledge when receptive understanding of all word family members is assumed from a correct response to an item assessing knowledge of just one family member; and the limited precision that a small, random sample of target words has in representing the population of words from which it is drawn. The article concludes that existing tests lack the accuracy needed for many specified testing purposes and discusses possible improvements going forward.